2020
DOI: 10.1080/20008198.2020.1815279
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study examining the mediational link between mild traumatic brain injury, acute stress, and post-traumatic stress symptoms following trauma

Abstract: Background : The presence of mild traumatic brain injury (mTBI) increases post-traumatic stress disorder (PTSD) symptoms in the months following injury. However, factors that link mTBI and PTSD development are still unclear. Acute stress responses after trauma have been associated with PTSD development. mTBI may impair cognitive functions and increase anxiety immediately after trauma. Objective : This research aimed to test the possibility that mTBI increases acute stress sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The current study is a part of a larger ongoing longitudinal neuroimaging study, and study procedure has been published previously (Shih et al , 2020; Chen et al , 2021). In brief, adult trauma survivors were recruited from the ED of two local hospitals within 48 h posttrauma.…”
Section: Methodsmentioning
confidence: 99%
“…The current study is a part of a larger ongoing longitudinal neuroimaging study, and study procedure has been published previously (Shih et al , 2020; Chen et al , 2021). In brief, adult trauma survivors were recruited from the ED of two local hospitals within 48 h posttrauma.…”
Section: Methodsmentioning
confidence: 99%
“…1 Accumulating evidence has revealed that PTSS severity is associated with multifaceted pre-, peri-and post-trauma risk factors, such as history of childhood maltreatment, presence of mild traumatic brain injury at the time of event and subsequent brain alterations in emotion neurocircuitry. [2][3][4][5] Notably, early post-traumatic stress responses that emerge within days to weeks post-trauma have been shown to be robust predictors of future development of PTSD. 6,7 These studies employed group-based variable-centred analytic methods to identify predictors of interest.…”
mentioning
confidence: 99%